1966
DOI: 10.1017/s0016672300009885
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of complementation data

Abstract: The evidence for complementation maps being linear is examined by analysis of all known complementation maps in micro-organisms, and by constructing maps from mutants randomly sampled from amongst those at the leu-2 locus in Neurospora with known complementing properties. Eleven loci out of thirty-five examined in six micro-organisms have non-linear complementation maps. Two linear maps, his-3 and ad-3b (having 25 and 35 complementation groups respectively) have a sufficiently large number of groups for it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1 was constructed following the rules outlined by Gillie (1966). It is a linear map composed of seven complemen-58 PETER S. CARLSON tation units and 16 complementation groups.…”
Section: Genetic Complementationmentioning
confidence: 99%
“…1 was constructed following the rules outlined by Gillie (1966). It is a linear map composed of seven complemen-58 PETER S. CARLSON tation units and 16 complementation groups.…”
Section: Genetic Complementationmentioning
confidence: 99%
“…Studies of several complementation maps ( GILLIE 1966( GILLIE ,1968 have shown that clustering of mutants occurs on these maps in a way which is consistent with the CRICK-ORGEL theory of complementation. Since no other suggestion has been made to account for this clustering, its existence lends some support to the theory.…”
mentioning
confidence: 75%
“…On the other hand, two mutations may complement although they both affect the determinant for a single polypeptide chain (CRICK and ORGEL 1964;GILLIE 1966). This intracistronic complementation is generally less efficient than intercistronic complementation.…”
Section: ) Complementation Groups and The Number Of Cistronsmentioning
confidence: 99%